De quelle origine est ce personnage? - Bouyoucas, Pan (Études helléniques / Hellenic Studies, 2005)
Thirty years afcer the publication of his first navel in 1975, Pan Bouyoucas is the only Greek-born novelist and playwright writing in French in Québec and Canada. In his testimony, he reflects on his journey as a writer, his choice of language, and the problems arising from that choice. Not because he is of another origin. There are many foreign-born francophones writing in Québec coday. Most of them, however, write about the "old country" or focus on their cultural community, while Bouyoucas, as noted by Maïr Verthuy, professor of literature at Concordia University, was for many years the only writer who always set his stories in Montréal and peopled them with characters of all origins. A task made all the more difficult by a majority which is hypersensitive to criticism, and, without really knowing the other, rejects any image which does not correspond to the one it has of him. As to the Greek community, because Bouyoucas wrices in French, it has ignored him totally.